Sustainable Biogas Development in Argosari Village: A Spatial, Environmental, and Economic Feasibility Analysis - Ghefra Rizkan Gaffara; Arfilian Permana Putra; Debby Syafriyandi; Raafi Widyaputra Yulianyahya; Ansadilla Niar Sitanggang (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
Energy transition at the village level plays a crucial role in Indonesia’s strategy toward sustainable energy independence. This research examines the biogas-based renewable energy development in Argosari Village as a model of community-driven sustainability. The study integrates qualitative and quantitative analyses—spatial, environmental, and economic—using IPCC guidelines, Location Quotient (LQ), Internal Rate of Return (IRR), and Net Present Value (NPV). The research involved interviews with 45 households, three focus group discussions with farmer associations, and secondary data from the Malang Regency Bureau of Statistics. Results show that 57% of households have installed biogas units, reducing GHG emissions by approximately 60% (1.2 tons CO₂ per household annually), and achieving a B/C ratio of 1.75. Sensitivity analysis indicates project feasibility remains positive even under ±15% variation in maintenance and subsidy levels. Comparative analysis with rural biogas programs in India and China highlights Argosari’s unique integration of social, economic, and environmental benefits. This study contributes a replicable framework for community-scale renewable energy implementation in rural Indonesia.